Law and Economics of Personalized Medicine Institutional Levers to Foster the Translation of Personalized Medicine - Bosshard, Karin (Gesundheitsmanagement und Gesundheitsökonomik,, 2018)
The book adds to the discussion about strategic approaches towards the translation of personalized medicine into clinical practice. It stresses the importance of non-science related, institutional barriers. A Law and Economics perspective is applied in order to examine the incentives induced by the barriers. An applied part identifies and evaluates policy levers to foster the translation of personalized medicine into Swiss clinical practice. The content • Overview of terminologies used in the context of personalized medicine • Description of personalized medicine's impact on the healthcare landscape • Identification and analysis of the institutional barriers to the translation of personalized medicine into clinical practice • Analysis of institutional barriers to the translation of personalized medicine in Switzerland • Identification and evaluation of institutional levers to foster the translation of personalized medicine into Swiss clinical practice Target groups • Social scientists with limited knowledge of personalized medicine, Law and Economics scholars, health economists • Practitioners in pharmaceutical, diagnostics and health insurance companies, healthcare policy makers and Swiss lawyers The author Dr. Karin Bosshard wrote this book during her time with a globally leading management consultancy where she was working as a strategy consultant. The author is currently working at an international pharmaceutical and diagnostics company and is a lecturer at the University of St. Gallen.